MiBee Braille Application: An Alternative Accessibility Literacy for Totally Blind Students at Inclusive School - Pahlawaty, Neddyana; Aprilia, Imas Diana (Angstrom Centre of Education, 2022)
The literacy ability of totally-blind students is still low. This is allegedly due to limited and conventional access of media. Alternative use of accessible media becomes an urgent thing to improve literacy ability for totally-blind students. The purpose of this research is to describe alternatively accessible media such as MiBee Braille for improving totally-blind students’ literacy ability. The method used is descriptive method with literature study analysis and supported by an observation one of totally-blind student. The result of this research is that the application can be used to write Braille with six-dot typing system, ten-finger typing system, and converts Ms. Word text into Braille text. Six-dot typing system makes totally-blind students easier to write other Braille symbols that cannot be found in Latin symbols.